Karakteristik Produksi Browns Gas Dengan Menggunakan Tenaga Matahari - Widhiyanuriyawan, Denny; Hamidi, Nurkholis; Wijono, Wijono (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Renewable energy has potentials to be developed to meet our energy needs in the future. One promising energy source is browns gas. Browns gas is a mixture of di-atomic and mono-atomic of hydrogen and oxygen. One effort to produce browns gas is through the process of electrolysis of water. However, the process of electrolysis still considered a process uneconomical and inefficient, since the energy of electrochemical decomposition of water is relatively high. Thus, the challenge of brown gas production is reducing electrical energy. In this study, we propose to use solar energy for browns gas production plant, since the solar energy is environmentally friendly energy sources available so abundant in Indonesia. The experiment was carried out in two methods. First, the electrolysis was done using electricity produced by the solar panel directly without voltage control. The second method, the voltage of electricity from the solar panel was controlled using a regulator then it used for the water electrolysis. The results show that the direct method generates fluctuative electricity with the rate power of 29.67 Watt. This electricity was used for electrolysis process and produced brown gas 0,1393 g for 4 hours. On the other hand the in-direct method generated power relatively constant at 18.3 Watt and produced the brown gas about 0.1365 g.Keywords: solar energy, browns gas, electrolysis, hydrogen